Dari Tradisi Tenun Lokal Menuju Harmoni Global - Fahimah, Siti (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study explores the weaving tradition of Pelangwot Village, Lamongan, as a representation of self-control and tolerance within an Islamic socio-cultural framework. Employing an Islamic social ethnographic approach with a descriptive–interpretative paradigm, it aims to interpret the symbolic, moral, and spiritual meanings embedded in the weaving practice. Data were collected through participatory observation, in-depth interviews, and documentation of cultural artifacts, and analyzed through thematic reduction, symbolic categorization, and reflective interpretation. The findings reveal that weaving is not merely an economic activity but also a spiritual discipline that cultivates the values of mujāhadah an-nafs (self-restraint), tasāmuh (tolerance), amānah (trustworthiness), and ihsān (excellence). The practice demonstrates the integration of work and worship, fostering an Islamic work ethic grounded in beauty, patience, and social responsibility. Despite digital transformation, the Pelangwot community maintains its spiritual integrity and collective ethos. In conclusion, the weaving tradition of Pelangwot embodies a form of living Islamic ethics—an expression of Islam rahmatan lil ‘alamin that harmonizes local productivity, spiritual consciousness, and global humanity